2013
DOI: 10.1111/dth.12099
|View full text |Cite
|
Sign up to set email alerts
|

A case of linear atrophoderma of Moulin successfully treated with methotrexate

Abstract: Linear atrophoderma of Moulin is an acquired rare and self-limited skin condition. It is characterized by atrophic bandlike skin lesions that often show hyperpigmentation and always follow the lines of Blaschko. Usually it begins in childhood or adolescence and there is no evidence of any long term progression. We describe a case of a 21-year-old woman with clinical and histological features of linear atrophoderma of Moulin. The patient was successfully treated with methotrexate 20 mg/week during 6 months with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“… 7 A case of LAM successfully treated with methotrexate 20 mg/wk for 6 months with an improvement of pigmentation and atrophy was reported. 8 The authors suggested that LAM, atrophoderma of Pasini and Pierini, and linear scleroderma may be a spectrum of a common disease entity in view of the response to methotrexate, which is an effective therapeutic option for morphea. However, some cases of LAM do not respond to potent topical steroids and topical calcipotriol, which are the first-line treatment for morphea.…”
Section: Discussionmentioning
confidence: 99%
“… 7 A case of LAM successfully treated with methotrexate 20 mg/wk for 6 months with an improvement of pigmentation and atrophy was reported. 8 The authors suggested that LAM, atrophoderma of Pasini and Pierini, and linear scleroderma may be a spectrum of a common disease entity in view of the response to methotrexate, which is an effective therapeutic option for morphea. However, some cases of LAM do not respond to potent topical steroids and topical calcipotriol, which are the first-line treatment for morphea.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of methotrexate was apparent in the short term for linear morphoea which is a similar condition with LAM. Thus, to this date, only one case report of LAM, for methotrexate treatment during 6 months, has shown measurable progressive regression, but little is known about the long‐term efficacy. A long‐term follow up should be done to assess sustained therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose penicillin, topical steroids, heparin and oral potassium benzoate have all been tried without success [ 6 ]. Recently, methotrexate was reported to partially improve the clinical appearance of widespread LAM in a 20 year old female [ 7 ]. However, its true effectiveness still remains to be ascertained.…”
Section: Discussionmentioning
confidence: 99%